A systematic mapping of test case generation techniques using UML interaction diagrams. Issue 6 (23rd December 2019) - Minhas, Nasir Mehmood; Masood, Sohaib; Petersen, Kai; Nadeem, Aamer
Abstract: Model‐based test case generation techniques provide a mechanism to derive tests systematically. This study provides a systematic mapping of test case generation techniques based on UML interaction diagrams. The study compares the test case generation techniques regarding their capabilities and limitations, and it also assesses the reporting quality of the primary studies. We can conclude that the studies presenting test case generation techniques using UML interaction diagrams were not following the guidelines for research methods (eg, case studies or experiments). Solutions were not empirically evaluated in industrial contexts. Our study revealed that better tool support is needed to introduce the UML interaction diagram–based test case generation techniques in the industry.